The Citation Practices of Doctorates in Economics - Stigler, George J.; Friedland, Claire (Journal of Political Economy, 1975)
The citations of doctorates in economics (who received the degree between 1950 and 1955) from six major universities are analyzed for articles published in the period 1950-68 in the two fields of value theory (microeconomics) and monetary and fiscal theory (macroeconomics). The citations are examined for commonality in the use of authorities and for parochialism with regard to the faculty of their Ph.D.-granting institution. The citation practices of the "authorities" cited by the doctorates are also examined, compared with those of the doctorates, and used to define scientific associates and adversaries.